A Project Report on Randomized Intrusion Tolerance Asynchronous Services - SACHIN K, SOUMAK K, SYED SUFYAN and AHMED MOW (2011)
INTERNAL GUIDE: ANNAPOORANI G, MVJCE
Keywords: Tolerance Asynchronous Services